Imitative inhibitory control is associated with psychotic experiences in a sample from the general population - Ulloa, José Luis; Núñez, Daniel E.; Gaspar, Pablo A.; Brass, Marcel (Frontiers in Psychiatry, 2024)
Psychotic experiences (PE) are prevalent and associated with several negative mental health outcomes in both clinical and general population, particularly in young people. A promising avenue to understand the mechanisms underlying PE is to investigate functions that may be related to specific neural systems. One of these key cognitive mechanisms is the ability to control our imitative responses, which is strongly linked to an adequate social functioning. Emergent evidence suggests that impairments in this function might be involved in the early expressions of psychosis, but few studies have investigated its association with PE in a sample from the general population. Using an imitation-inhibition paradigm we examined this relationship in a community sample of young healthy individuals (N=204) and found that increased levels of PE levels were associated with lower imitative inhibitory control. These effects seem to be specific to imitation-inhibition as no correlation was found for a more general cognitive control as addressed by a Stroop-like task. In addition, these effects seem to be more evident for paranoid ideations. Overall, our results suggest that imitative inhibitory control can serve as a proxy to detect abnormalities associated with psychotic experiences.